STUDI KEPEMIMPINAN PROF. IMAM SUPRAYOGO DALAM MENGIMPLEMENTASIKAN PERUBAHAN KELEMBAGAAN UIN MAULANA MALIK IBRAHIM MALANG - Imam Muslimin (lp2m-uin malang, 2011)
There are three forces that drive the organization make a change, namely: (1) external forces, (2) the internal strength, and (3) change agent. This means that each change was influenced by three things and the three forces that have their respective roles and inter-related from each other. Changes in any uncertain terms directly running smoothly. And when there is dynamic development of various facets of life, change is a must. It is not easy to make changes from the status quo to progression, particularly those involving changes in mindset. And to change it to walk toward the positive points, needed a leader who is able to socialize and internalization of the change effectively.Keywords: leadership, institutional change and socialization